Assessing the Digital Citizenship Self-efficacy of Pre-service Teachers - Wanicha Sakorn (Journal of Educational Issues, 2024)
In this study, we aim to assess pre-service teachers’ self-efficacy in using computer technology in the digital era as digital citizens. Briefly, students in the Faculty of Education were asked how they perceive computers and technology as a tool in life, education, and future careers. The samples were 615 pre-service teachers selected by Yamane’s method in sample selection from the population of 3093 students in the Faculty of Education, Rajabhat Maha Sarakham University, Thailand. The samples were 1-5th year student teachers from 20 majors in the faculty. The samples were from middle to upper-middle-income families considering the public status of the university with the tuition fee of around 350-400 USD a semester. The sole instrument of the study was a questionnaire with the purpose to investigate computer self-efficacy as digital citizens of the samples. The data were collected in 2020 via an online questionnaire and analyzed by percentage, mean score, standard deviation, t-test, and one-way ANOVA. The results of the study lead to an explanation of the nature of prospective teachers’ beliefs and willingness to develop themselves as a member of the post-digital world, a place where a blurred area of virtual and authentic exist and affect people’s lives. It shows that pre-service teachers of a certain socio-economy group had a high level of digital citizenship self-efficacy.